Peran Moderasi Literasi Digital Pada Efektivitas Penggunaan Sistem Informasi Akuntansi Dan Literasi Keuangan - Muhammad Fathan Mubina; Hairul Triwarti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The financial performance of Micro, Small, and Medium Enterprises (MSMEs) is an important aspect to be examined, considering its strategic role in supporting economic growth, particularly in the e-commerce–based business sector. This study aims to analyze the effect of the effectiveness of Accounting Information Systems (AIS) usage and financial literacy on the financial performance of MSMEs, as well as to examine the role of digital literacy as a moderating variable. This research employs a quantitative approach with the research object consisting of e-commerce–based MSME actors operating in the South Tangerang area. Data collection was carried out through the direct distribution of questionnaires to respondents who met the research criteria. The collected data were analyzed using moderating regression analysis to examine the relationships among the research variables. The results indicate that the effectiveness of AIS usage and financial literacy have a positive effect on the financial performance of MSMEs. In addition, digital literacy is proven to moderate the relationship between the effectiveness of AIS usage and financial literacy on the financial performance of MSMEs. These findings indicate the importance of enhancing digital literacy, effectively utilizing accounting information systems, and strengthening financial literacy to improve the financial performance of e-commerce–based MSMEs.